2009
DOI: 10.1002/hyp.7225
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic Oscillation influences on Turkish lake levels

Abstract: Abstract:The North Atlantic Oscillation (NAO) is a large-scale mode of natural climate variability governing the path of Atlantic mid-latitude storm tracks and precipitation regimes in the Atlantic and Mediterranean sectors. The primary focus of this study is to investigate the variability of lake levels in seven lakes scattered across Turkey using the method of continuous wavelet transforms and global spectra. The long winter (December, January, February and March) lake-level series and the NAO index (NAOI) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…(2010), periodicities of more than 10 years, more frequent in the northern region, are difficult to relate with the NAO. This was also concluded by Kücük et al (2009) for Turkey. Following the results reported by Tsiropoula (2003) and Hathaway (2010), these multidecadal cycles may relate to solar cycles.…”
Section: Discussionsupporting
confidence: 62%
“…(2010), periodicities of more than 10 years, more frequent in the northern region, are difficult to relate with the NAO. This was also concluded by Kücük et al (2009) for Turkey. Following the results reported by Tsiropoula (2003) and Hathaway (2010), these multidecadal cycles may relate to solar cycles.…”
Section: Discussionsupporting
confidence: 62%
“…In the Mediterranean area, a correlation between the NAO, precipitation, river discharges and lake levels was also found in the Middle East and in Turkey (Cullen and deMenocal, 2000;Cullen et al, 2002;Karabörk et al, 2005;Türkes and Erlat, 2005;Kücük et al, 2009). A strong interdependence among the NAO, precipitation, river discharges and air temperature in some southern Italy regions (Brandimarte et al, 2011;Caloiero et al, 2011) was discovered.…”
Section: Introductionmentioning
confidence: 91%
“…In the Mediterranean region a negative relationship between the NAO and river discharges has been found in the Middle East (Cullen and DeMenocal, 2000;Cullen et al, 2002) and in Turkey (Karabörk et al, 2005;Kalayci and Kahya, 2006), where lake levels have also been related to the NAO (Kücük et al, 2009). Within the Iberian Peninsula (hereafter IP) the influence of the NAO on river discharges has been analyzed in studies of various basins (López-Moreno et al, 2007;Trigo et al, 2004;Morán-Tejeda et al, 2011), where reasonably high correlations have been found between the NAO and streamflows, particularly in winter.…”
Section: Introductionmentioning
confidence: 99%